2023
DOI: 10.1038/s41588-023-01410-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association meta-analysis of spontaneous coronary artery dissection identifies risk variants and genes related to artery integrity and tissue-mediated coagulation

Abstract: Spontaneous coronary artery dissection (SCAD) is an understudied cause of myocardial infarction primarily affecting women. It is not known to what extent SCAD is genetically distinct from other cardiovascular diseases, including atherosclerotic coronary artery disease (CAD). Here we present a genome-wide association meta-analysis (1,917 cases and 9,292 controls) identifying 16 risk loci for SCAD. Integrative functional annotations prioritized genes that are likely to be regulated in vascular smooth muscle cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…Elevated polygenic risk in those with familial disease vs controls has been reported in many complex diseases; notably, in this study, almost half of all affected family members scored in the top quintile of control scores. This is in line with our recent finding that the common variant heritability of SCAD is high in individuals with sporadic SCAD . In other complex conditions, it has been proposed that a high PRS confers an OR for disease that is comparable with a single rare pathogenic variant .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Elevated polygenic risk in those with familial disease vs controls has been reported in many complex diseases; notably, in this study, almost half of all affected family members scored in the top quintile of control scores. This is in line with our recent finding that the common variant heritability of SCAD is high in individuals with sporadic SCAD . In other complex conditions, it has been proposed that a high PRS confers an OR for disease that is comparable with a single rare pathogenic variant .…”
Section: Discussionmentioning
confidence: 99%
“…To address this, we created 1000 seven-SNV scores using the height PRS, and very rarely across the following 1000 analyses did we identify results of the magnitude reported for the SCAD PRS. Ideally, a larger, more sophisticated PRS created from a larger SCAD genome-wide association study would be used; however, due to sample overlap between this study and the current largest SCAD genome-wide association study, this is not currently possible. While the main conclusions were robust in all scenarios, validation of these results with larger independent cohorts and more sophisticated SCAD PRS remains important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…63 A recent GWAS for spontaneous coronary artery dissection found that risk variants were disproportionately enriched within open chromatin regions in VSMCs and fibroblasts. 64 Similar experiments in aortic cell lines and human tissues undoubtedly have the potential to offer fresh insights into the epigenomic landscape of aortic disease.…”
Section: Locus Prioritizationmentioning
confidence: 99%